Analisis Model Project Based Learning Dalam Meningkatkan Hasil Belajar IPAS Siswa Di SD Negeri 75 Palembang - Dyah Resti Paramita; Farhan Yadi; , Imelda Ratih Ayu (Journal of Practice Learning and Educational Development, 2025)
This study aims to determine and describe how the implementation of the Project Based Learning (PJBL) Model can improve student learning outcomes in the Natural and Social Sciences (IPAS) subject in grade IV of State Elementary School 75 Palembang. The methods used in this study were observation, interviews, and documentation. The results showed that the implementation of the PJBL Model had a positive impact on the process and learning outcomes of students. Students became more active, enthusiastic, and motivated during the learning process. The PJBL steps implemented by the teacher—starting from determining basic questions, planning, implementation, to project presentation—have encouraged students to think critically, work together, and build knowledge independently. The average student score increased from the sufficient category (50–60) to good to very good (70–90). In addition, PJBL also supports the development of soft skills such as collaboration, communication, and responsibility. The results of this study indicate that the PJBL Model is effective in improving science learning outcomes and creating a more interesting and meaningful learning experience for students.